Patient Experiences of Bullous Pemphigoid: Symptoms and Health-Related Quality of Life Impacts - Calvin N. Ho; Lila Bahadori; Marc Yale; Naomi Bishop; Caroline Roberts; Oren Meyers; Julie Bailey; Neil J. Korman (Dermatology and Therapy)
Abstract Introduction Bullous pemphigoid (BP) is a chronic autoimmune blistering disorder that imposes a significant health-related quality of life burden on the lives of patients; however, there are limited data on patient experiences. Methods We conducted qualitative open-ended interviews of patients from the USA, Spain, and France, to understand BP symptoms and impacts, and develop a conceptual model. Adults with a confirmed BP diagnosis were included. Patients with pemphigus or drug-induced BP were excluded. Results Thirty participants were recruited. The mean (standard deviation) age was 63.6 (16.0) years. Eleven signs and symptoms and 24 impacts were reported; six signs and symptoms, and 13 impacts affected ≥ 50% of participants with an average disturbance rating of ≥ 5 out of 10 (scale of 0 to 10 [0, not disturbing; 10, extremely disturbing]). All participants reported typical signs and symptoms of classic and/or mucosal BP. Overall, five of six salient symptoms and four of 13 salient impacts had an average disturbance rating of ≥ 7.5/10, indicating that BP is highly burdensome. Regarding corticosteroids, participants expressed a strong desire to avoid taking them again, due to the associated unwanted side effects. Conclusion The conceptual model presented here can be the basis for endpoint selection in studies of new therapies for BP.